Incidence of oral potentially malignant disorders requiring surgical excision in young vs elderly populations (Academia Journal of Medicine, 2025)
Aim To compare the incidence and clinical presentation of oral potentially malignant disorders (OPMDs) necessitating surgical excision in younger and older populations, and to assess age-related variations in lesion characteristics, surgical outcomes, and potential risk factors.Methods Across-sectional observational study was performed on 100 patients who underwent surgical excision of oral potentially malignant disorders (OPMDs). Patients were categorised into two groups: young (n=40) and elderly (n=60). Demographics, risk factors, lesion characteristics, histopathology, and postoperative outcomes, including recurrence and malignant transformation, were documented. Statistical analysis encompassed descriptive statistics, Chi-square tests, and logistic regression; a p-value of
Keywords: Oral potentially malignantdisorders , Oral submucous fibrosis, Leukoplakia, Dysplasia, Age related differences, Surgical excision